2021
DOI: 10.25273/pe.v11i1.7817
|View full text |Cite
|
Sign up to set email alerts
|

Development of mind mapping-based comics to improve math learning outcomes

Abstract: <div><p>This study aims to develop, study the feasibility and effectiveness of mathematics comic media based on <em>mind mapping</em> for fifth-grade students of public elementary schools in Demak. The method used is the Sugiyono Research and Development model consisting of 7 steps. The data analysis technique used descriptive statistics, t-test, z-test and n-gain. The results showed the development process of mathematical comic media based on mind mapping on speed and discharge topics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…et al 2018) Borg and Gall model has ten steps in developing instructional model and media including potential and problems, data collection, developing initial products, initial field testing, product revision, field trial, revision, operational field test, final product revision and product destination and implementation. However, the researcher of this study conducted only seven steps of the procedure (Trimurtini, et al 2021).…”
Section: Randd Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…et al 2018) Borg and Gall model has ten steps in developing instructional model and media including potential and problems, data collection, developing initial products, initial field testing, product revision, field trial, revision, operational field test, final product revision and product destination and implementation. However, the researcher of this study conducted only seven steps of the procedure (Trimurtini, et al 2021).…”
Section: Randd Modelsmentioning
confidence: 99%
“…The studies on comics found in educational journals in Indonesia mostly focus on how to design and develop instructional comics which are then utilized in the learning process. Some of the studies utilized created comics as a material resource and they effectively were to improve student's learning outcomes (Trimurtini et al, 2021;Maryani, et al, 2018 because comics are interesting and produce good learning atmosphere (Fatimah, et al 2019). Notwithstanding, among all these studies, none of which attempts to either choose existing educational comics as a resource or employ comics in the classroom to evolve students in creating as a product of project-based learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sebagai pemimpin suatu _______________ lembaga, kepala sekolah harus memiliki jiwa kepemimpinan yang baik dalam menjalankan tugasnya sebagai seorang pemimpin. 34 Kepemimpinan kepala sekolah dituntut untuk mulai mendapatkan pekerjaan sebagai kepala sekolah. Kepemimpinan kepala sekolah sangat berperan dalam keberhasilan pelaksanaan program yang telah direncanakan untuk mencapai tujuan pendidikan di sekolah tersebut.…”
Section: Membentuk Gugus Tugas Covid 19unclassified
“…In the national curriculum, mathematics is a lesson that can support the development of science and technology and also contribute to problem-solving abilities (Bature et al, 2020;Trimurtini et al, 2021). However, most teachers still teach mathematics monotonously, which makes students think that learning mathematics is boring.…”
Section: Introductionmentioning
confidence: 99%